Not about rules, but about good deals: The political economy of securing inclusive capital investment and transformation in South African mining - Nxele, Musawenkosi (School of Economics, 2023)
This PhD studies the imperative of racially transforming South Africa's economy in a way that spurs the growth of capital investment that is socially and locally inclusive. Part I explores the role of bargains among elites (“deals”) in facilitating investment. It studies deals as the basis of credible commitment and as the “arena of action” in the context of a relatively robust rule of law. What kind of deals produce capital investment and transformation, and what kind of deals produce predation and isomorphism? Using process tracing methodology, the research traces deal in platinum mining between 1994 and 2018. Part II examines the extent to which this investment is socially inclusive in alleviating local poverty, creating local employment, and reducing local inequality. This part relies on individual level census data of 20 million observations and geocoded mining data of over 400 mines to evaluate the local impact of mining investments on income poverty, employment, and inequality between 1996 and 2011. The study finds compelling evidence that “deals are the basis of credible commitment” to securing investment. The rule of law alone is important but insufficient as it leaves “residual uncertainty” for investors. The evaluation of the impact of mining investments on local communities suggests a qualification, at the local level, of the “resource curse” hypothesis. Mining brings benefits in terms of income poverty alleviation and employment. However, the high-low cycles of commodity price booms create employment volatility and exacerbate inequality. Mining investments inherently involve trade-offs that can be moved in net positive directions with good deals between business and the state, and local communities. The research thus contributes to the literature on property rights and investment, state-business relations and development, and natural resource governance for development.